2019
DOI: 10.1007/s00493-018-3765-6
|View full text |Cite
|
Sign up to set email alerts
|

The Number of Triple Systems Without Even Cycles

Abstract: For k 4, a loose k-cycle C k is a hypergraph with distinct edges e 1 , e 2 , . . . , e k such that consecutive edges (modulo k) intersect in exactly one vertex and all other pairs of edges are disjoint. Our main result is that for every even integer k 4, there exists c > 0 such that the number of triple systems with vertex set [n] containing no C k is at most 2 cn 2 .An easy construction shows that the exponent is sharp in order of magnitude. This may be viewed as a hypergraph extension of the work of Morris … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 56 publications
(84 reference statements)
2
15
0
Order By: Relevance
“…for any fixed r, k ≥ 3. Since the lower bound in (1) is generally believed to be closer to the truth, Mubayi and Wang [12] made the natural conjecture that…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…for any fixed r, k ≥ 3. Since the lower bound in (1) is generally believed to be closer to the truth, Mubayi and Wang [12] made the natural conjecture that…”
Section: Introductionmentioning
confidence: 97%
“…Consequently, as in the case of graphs, it is important to understand the behaviour of prototypical examples of r-partite r-graphs. Here, following Mubayi and Wang [12], we shall investigate the enumeration problem for one such prototypical family of r-partite r-graphs, namely, the family of r-uniform linear (or loose) cycles.…”
Section: Introductionmentioning
confidence: 99%
“…for every r,3. Guided and motivated by this development on the extremal numbers of linear cycles, recently, Mubayi and Wang showed that Forb3(n,C3)=2O(n2) for all even and improved the trivial upper bound in for r>3. Inspired by Mubayi and Wang's method, Han and Kohayakawa subsequently improved the general upper bound to 2O(nr1loglogn).…”
Section: Introductionmentioning
confidence: 99%
“…Guided and motivated by this development on the extremal numbers of linear cycles, recently, Mubayi and Wang showed that Forb3(n,C3)=2O(n2) for all even and improved the trivial upper bound in for r>3. Inspired by Mubayi and Wang's method, Han and Kohayakawa subsequently improved the general upper bound to 2O(nr1loglogn). Very recently, Balogh, Narayanan, and Skokan provided a balanced supersaturation theorem for linear cycles and finally proved Forbr(n,Cr)=2O(nr1), for every r,3, using the hypergraph container method .…”
Section: Introductionmentioning
confidence: 99%
“…The idea of investigating Question 6 was suggested in a recent work of Mubyai and Wang [36]. They conjectured that Question 6 has an affirmative answer in the case when H is C (r) k , the r-uniform expansion 3 of C k , the (2-uniform) cycle of length k. Improving upon the result from [27,36], Balogh, Narayanan, and Skokan [7] have recently solved the conjecture of Wang and Mubayi. As immediate corollaries from Theorem 7 we reprove this result along with two related estimates for expansions of paths and complete bipartite graphs.…”
Section: Introductionmentioning
confidence: 99%